Preclinical development of a standardized extract of Ilex paraguariensis A.St.-Hil for the treatment of obesity and metabolic syndrome - Sara E.L. Tolouei; Rodrigo Marcon; Fabiana Cardoso Vilela; Cristina Setim Freitas; Melina Heller; Edineia Lemos de Andrade; Sergio José Macedo Júnior; Adara Áurea dos Santos; Ruth Fernandes Rocha; Guilherme Pasetto Fadanni; Naiani Ferreira Marques; Jarbas Mota Siqueira Júnior; et al. (Pharmacological Research)
Obesity is a global epidemic often associated with serious medical complications such as diabetes, hypertension and metabolic dysfunction-associated steatohepatitis. Considering the multifactorial nature of these diseases, medicinal plants could be a valuable therapeutic strategy as their phytoconstituents interact with multiple and relevant biological targets. In this context, Ilex paraguariensis emerges as a potential alternative to treat obesity and associated metabolic diseases since several studies have demonstrated its anti-inflammatory, anti-obesity and anti-diabetic effects. We present a comprehensive and complete non-clinical investigation of the efficacy, safety and putative mechanisms of action of a standardized aqueous extract of I. paraguariensis (TI-076). We also describe a scalable preparation of TI-076 and demonstrate its long-term stability. TI-076 exhibits long-term stability and its major constituents are well absorbed orally in mice and rats. The five in vivo proofs of concept studies revealed that TI-076 reduced obesity, hyperglycaemia, blood pressure, liver fat accumulation, levels of serum insulin, leptin and cholesterol, food intake, inflammation and increased GLP-1 levels. The mechanisms through which TI-076 acts seem to involve the modulation of several genes associated with inflammation (Il1b, Nlrp3, Pparα and Pparγ), white adipose and liver metabolism (Cartpt, Mgll, Ramp3, Faah, Cck, Clps, Pparα and Pparγ), liver damage and fibrosis (Creb1, Col1a1 and Col3a1). Finally, TI-076 did not interact with CYP3A4 in vivo and proved to be safe. These findings strongly suggest that TI-076 holds great potential for clinical trials aimed at developing a safe phytomedicine for treating obesity and related metabolic diseases.